(untitled) (Baghdad Science Journal, 2020)
The present study aimed to determine the serum sex hormone levels among Benign Prostatic Hyperplasia (BPH) patients before and after 3 months of oral administration of 5-α reductase inhibitor(finasteride). Forty BPH patients and 40 healthy men from Amara city were involved in this study, their ages were between 40-59 year. They were all subjected to direct estimation of hormones by MinVidas method including Testosterone (T), Estradiol (E2), Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), Prolactin (PRL), and Dihydrotestosterone (DHT) before and after 3 months of treatment with 5α-reductase inhibitor (finasteride) (the healthy individuals didn’t take finasteride).The results showed that T level was significantly lower (P<0.05) in pre-treated compared to the post-treated patients and control group, whereas no significant difference was observed between the two latter groups. Levels of E2 - and DHT were significantly lower (P<0.01) in post-treated compared to the pre-treated patients with no significant difference with control group, while they were significantly higher (P<0.01) in pre-treated patients compared to control group. FSH and LH levels showed no significant differences in the pre-treated in comparison with post-treated and control groups. PRL levels insignificantly higher in pre-treated in comparison with post-treated patients, while significantly higher (P<0.05) in comparison with control group, with the later showing a significant lower (P<0.05) in comparison with post-treated patients. It is concluded that 5α-reductase inhibitor (finasteride) plays a role in decreasing levels of DHT and E2 which have vital roles in enlargement of prostate.